PENGARUH AFIKASI DIRI, PERSEPSI RISIKO, DAN MODAL MINIMAL PADA MINAT MAHASISWA BERINVESTASI CRYPTOCURRENCY - Wardhana, Ngurah Adhitya Warma; Putri, I Gusti Ayu Made Asri Dwija (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.14.NO.05.TAHUN.2025DO - 10.24843/EEB.2025.v14.i05.p08, 2025)
In recent years, cryptocurrency has become an attractive investment option in Indonesia. However, the FTX global crypto exchange fraud case caused a decline in the interest of investors in Indonesia to invest in cryptocurrency. Several years since the FTX crypto exchange fraud case, the interest of investors and potential investors, especially students to invest in crypto exchanges has increased again. This study was conducted to seek empirical evidence regarding students' interest in investing in cryptocurrency. The focus of the research is directed at active students from the Accounting Study Program at the three best universities in Bali based on uniRank rankings. The selection of respondents was carried out using a proportionally stratified random sampling approach which resulted in 281 respondents from the total population. After the data were collected, the data were analyzed using multiple linear regression techniques. The findings of this study show that self-efficacy and the availability of initial capital have a positive effect on students' interest in investing in crypto assets. Conversely, the lower the level of risk perception, the greater the interest of students to engage in cryptocurrency investment.